Durability of the moderate-to-heavy-intensity transition is related to the effects of prolonged exercise on severe-intensity performance - Hamilton, K.; Kilding, A. E.; Plews, D. J.; Mildenhall, M. J.; Waldron, M.; Charoensap, T.; Cox, T. H.; Brick, M. J.; Leigh, W. B.; Maunder, E. (European Journal of Applied Physiology, 2024)
Purpose Power output at the moderate-to-heavy-intensity transition decreases during prolonged exercise, and resilience to this has been termed `durability`. The purpose of this study was to assess the relationship between durability and the effect of prolonged exercise on severe-intensity performance, and explore intramuscular correlates of durability.